Tingkat Kapasitas Petani dalam Pengembangan Kakao di Kabupaten Kolaka Timur - Putu Arimbawa; Mardin Mardin (Fakultas Pertanian Universitas Halu Oleo, 2021)
The capacity of farmers is closely related to the readiness of farmers to accept changes in innovation technology. The development of cocoa cultivation innovation technology for cocoa cultivation requires increasing the capacity of farmers to be able to respond appropriately to innovation in supporting cocoa development. The purpose of this study was to analyze the level of farmer capacity in cocoa development. The research was carried out in four cocoa center sub-districts in East Kolaka Regency from June to August 2019. Data was collected through structured interviews with 267 cocoa farmers and in-depth interviews with key farmers and agricultural extension workers. Data analysis was done descriptively. The results showed that the level of farmer's in cocoa development was in the medium category on the ability to manage farming resources, the ability to organize farming, the ability to adapt to innovation and the ability to evaluate innovation. The ability of farmers in organizing farming has the lowest ability compared to the other three capacity indicators so it needs to be improved